Impact of interfaces on bipolar resistive switching behavior in amorphous Ge–Sb–Te thin films. (27th February 2020) - Bryja, Hagen; Grüner, Christoph; Gerlach, Jürgen W; Behrens, Mario; Ehrhardt, Martin; Rauschenbach, Bernd; Lotnyk, Andriy
Abstract: Electrochemical metallization memories have received much attention as candidates for next generation non-volatile memory applications, due to their fast switching speed, simple structure, high scalability and low energy consumption. Chalcogenide compounds like Ge–Sb–Te-based materials are extensively studied solid electrolytes for such devices and considered within the most promising candidates. In this work, the influence of different electrode materials on bipolar resistive switching characteristics of amorphous Ge–Sb–Te thin films with close composition to 2:2:5, prepared by pulsed laser deposition, is studied. Detailed investigations by current-voltage measurements, secondary ion mass spectrometry and cross-sectional transmission electron microscopy in conjunction with energy-dispersive x-ray spectroscopy are presented. Depending on the utilized electrode material, analog switching (Cu, Ag, Ti), digital switching (Co, Cr, Ta, Al) or no switching (Pt, Au and Cr-CrO x ) occurs. This work shows that the switching behavior of Ge–Sb–Te strongly depends on the solubility and reactivity of the electrode material.